2014
DOI: 10.1161/strokeaha.114.004672
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Is Associated With Higher Death and Disability in Patients With Acute Ischemic Stroke

Abstract: ResultsA total of 372 223 (5.3%) patients admitted with AIS had ARF. Dialysis was required in 2364 (0.6%) of 372 223 patients. Patients with ARF were older (mean age, 74±28 versus 72±31 years; P<0.0001) and predominantly men (52%; P<0.0001). Comorbid conditions, such as hypertension, diabetes mellitus, atrial fibrillation, and congestive heart failure, were significantly higher in patients with ARF (Table I in the online-only Background and Purpose-Acute renal failure (ARF) in setting of acute ischemic stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 11 publications
4
44
1
Order By: Relevance
“…Our study findings are similar to the previously published literature on the outcomes of acute ischemic stroke with the accompanying AKI [6]. In this study, higher odds of mortality, disability, mean hospital charges and increased length of stay were reported; these factors are quite similar to our findings in a different cohort of patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study findings are similar to the previously published literature on the outcomes of acute ischemic stroke with the accompanying AKI [6]. In this study, higher odds of mortality, disability, mean hospital charges and increased length of stay were reported; these factors are quite similar to our findings in a different cohort of patients.…”
Section: Discussionsupporting
confidence: 92%
“…AKI can be seen in 5.3% of patients with ischemic stroke [6]. In our study, incidence of AKI was around 3.8% in patients admitted with TIA.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In addition to the threefold increase in mortality after AIS, acute kidney failure has been associated, after adjusting for confounding factors, with higher odds of moderate-to-severe disability and with ICH [23]. Furthermore, none of the studies in this meta-analysis included patients with acute kidney failure requiring dialysis, which may be associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…15 Multivariate analyses stratified by stroke type demonstrated that AKI was associated with significantly increased hospital mortality from ischemic stroke but not ICH. In a subsequent cross-sectional study from NIS, Saeed et al 16 examined the effect of AKI after AIS on risk of ICH and disability at discharge. Patients (5.3%) admitted with AIS had AKI, as defined by administrative codes.…”
Section: Discussionmentioning
confidence: 99%